One year measurements of vertical profiles of wind speed and wind direction from 40 to 500 m at Clausthal, Harz Mountains, Germany - Rausch, Thomas; Schuchard, Malte; Cañadillas, Beatriz; Lampert, Astrid (PANGAEA, 2022)
A Doppler windLiDAR (WindCube WLS8-8 [1] from the manufacturer Leosphere, France) was installed at Clausthal (51°47'58.48''N 10°21'7.42'′E, 595 m altitude) in the Harz Mountains, Germany, and operated continuously for a period of nearly an entire year (from 29 October 2014 to 26 October 2015). The wind LiDAR provided the vertical profiles of wind speed and wind direction, measured by means of the Doppler Beam Swinging technique. Four lines of sight are sequentially scanned by a 1.54 µm pulsed fiber laser to perform the geometrical computation of the 3D wind vector components. From the raw data, the average horizontal wind speed and wind direction is calculated routinely for intervals of 10 min. The wind LiDAR continuously collected profiles of wind speed and wind direction at 24 altitudes (40 m to 500 m, with a vertical resolution of 20 m). Data gaps are mainly caused by low clouds and fog, which cannot be penetrated by the laser pulses.
Keywords: Lidar; vertical profile; wind